Combination Of Schroth Exercise With Brace On Acceleration Of Cobb Angle Changes In Case Of Scoliosis : Literature Review - Nabilah Putri Mahdani; Riza Pahlawi (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
To evaluates the effectiveness of schroth exercise with a brace to accelerate changes in the cobb angle in cases of idiopathic scoliosis. This study is a literature review study with a narrative method. The research was conducted by tracing and analyzing articles relevant to the topics raised. The data used in this research is secondary data. Sources of secondary data obtained in the form of articles or journals relevant to the topic using the Pubmed, Proquest, and Google Scholar databases using the keywords